Environmental DNA: Preliminary Characterization of Microbiota in Three Sicilian Lakes - Mauro, Manuela; Villanova, Valeria; Valvo, Mario Lo; Alduina, Rosa; Radovic, Slobodanka; Vizzini, Aiti; Orecchio, Grazia; Longo, Francesco; Badalamenti, Rosario; Ferrantelli, Vincenzo; Cammilleri, Gaetano; Mauro, Annamaria; et al. (Ecology and evolution, 2025)
ABSTRACT Freshwater ecosystems play a key role in biogeochemical cycles and face various anthropogenic impacts. Understanding microbial communities within these ecosystems is crucial for ecosystem management and conservation. This study conducted a metabarcoding analysis of the bacterial 16S rDNA of environmental DNA (eDNA) to investigate the microbial diversity and composition in three Sicilian lakes (Poma, Piana, and Scanzano). The results revealed a common core microbiota in all the lakes, with Poma and Piana showing similar compositions, followed by Scanzano. Key bacterial phyla identified as core members across the sampled sites included Actinobacteriota, Proteobacteria, Bacteroidota, Verrucomicrobiota, Planctomycetota, and Cyanobacteria. Additionally, specific bacterial families such as Comamonadaceae, Burkholderiaceae, Ilumatobacteraceae, and Sporichthyaceae uniquely contributed to the microbial community structures. eDNA demonstrates potential as a quicker and less invasive tool to investigate biodiversity studies for these sites. The findings illuminate the intricate microbial dynamics within Sicilian freshwater ecosystems and emphasize the importance of considering microbial diversity in freshwater conservation and management strategies. Microbial content depends on the origin of the sample. This figure shows the relative abundance of bacteria in three lakes (Poma, Piana, and Scanzano) in Sicily, giving the first insights into microbial communities residing in those environments.